2008
DOI: 10.1007/s00395-008-0697-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term thyroid hormone administration reshapes left ventricular chamber and improves cardiac function after myocardial infarction in rats

Abstract: Thyroid hormone (TH) is critical for tissue differentiation at early stages of development, induces physiological hypertrophy and regulates the expression of important contractile proteins such as myosin heavy chain (MHC) isoform and calcium cycling proteins. Furthermore, TH seems to control the response to stress by regulating important cardioprotective molecules such as heat shock proteins (HSPs). Thus, the present study investigated whether TH administration immediately after acute myocardial infarction can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 42 publications
7
86
0
16
Order By: Relevance
“…On the other hand, our data indicate that Low-T3S persistence favors cardiac disease evolution and confirmed that, to be effective on adverse remodeling, the timing of Low-T3S correction should encompass the regenerative window that is lost in the late postischemic phase (48). In accordance, T3 replacement initiated 1 wk after MI improved ventricular performance without reversing cardiac remodeling (28), whereas THs administered early after I/R improved cardiac function and prevented LV chamber remodeling (17,30,31,47). However, the effectiveness of THs on cardiac geometry and function has also been reported in rats with old myocardial infarction (49).…”
Section: Disclosuresupporting
confidence: 76%
See 2 more Smart Citations
“…On the other hand, our data indicate that Low-T3S persistence favors cardiac disease evolution and confirmed that, to be effective on adverse remodeling, the timing of Low-T3S correction should encompass the regenerative window that is lost in the late postischemic phase (48). In accordance, T3 replacement initiated 1 wk after MI improved ventricular performance without reversing cardiac remodeling (28), whereas THs administered early after I/R improved cardiac function and prevented LV chamber remodeling (17,30,31,47). However, the effectiveness of THs on cardiac geometry and function has also been reported in rats with old myocardial infarction (49).…”
Section: Disclosuresupporting
confidence: 76%
“…Furthermore, clinical studies have shown that levels of T3 have a positive correlation with ejection fraction (EF%) in ST-elevation myocardial infarction (STEMI) patients at 48 h from the index event (22). Consistently, treatment of Low-T3S exerts cardioprotective effects in both humans and animal models and may be a novel option for treatment of cardiac disease (23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Experimental Protocolmentioning
confidence: 92%
See 1 more Smart Citation
“…5 It is likely that reexpression of the fetal gene program in the overloaded ventricle, a common feature of cardiac disease, is enhanced by low tissue TH levels. Pantos and colleagues [51][52][53][54][55] have published numerous animal studies on the effects of THs on the heart, particularly during ischemia or MI. They have shown that short-and long-term T3ϩT4 treatment of rats with MI leads to improved LV function and remodeling.…”
Section: Th Metabolism During the Early Post-mi Phasementioning
confidence: 99%
“…Las áreas diastólicas (AD) y sistólicas (AS) del VI se midieron en el modo bidimensional, por medio de planimetría, en dos líneas paraesternales: eje largo y eje menor. El índice de esfericidad se determinó al dividir el área diastólica obtenida en el eje mayor por el área diastólica obtenida en el eje menor, y el índice de estrés de la pared ventricular izquierda se determinó por la fórmula: (área diastólica/2 x HDVI) 21 . La función sistólica del VI se evaluó al calcularse la fracción de variación de área (FVA=AD-AS/AD x 100) 20 .…”
Section: Estudio Ecocardiográficounclassified